Choice of an Outdoor Game by mixed one Parametric IF Measures - Anita Singla, Vinod Kumar; Rupa Rani Sharma (International journal of economic perspectives, 2022)
Sports are considered not only to give pleasure to players, but the game must have some positive values. Games are attractive because the game played usually consider the interesting user interface and affect the human emotion also. One of the most important benefits for playing games is that the development of the human brain can be done. The physical fitness of the player is another important benefit of playing games (outdoor). The game itself is a system in which players are involved regularly and the prevailing culture in it, also the player interacts with the system. The success or failure of any team lies in the abilities and skills of the players that enclose the team. The process of game selection and team formation in multi-player sports is a complex problem where the ultimate success is determined by how the group of players forms an effective team. In general, the selection of the game and formation of the team for outdoor games are mainly judgments made by the influencing factors. An analytical model has developed to select an outdoor game by keeping the influencing factors in mind. In the whole analysis process, we propose two phase frameworks. For selection of game and player who want to play the game (outdoor) according to the game strategies and his interest. A case study is used to demonstrate the performance of the proposed approach.